International use of laughter in bonobos and chimpanzees? - Van Mulders, Laura (Neuchâtel : Université de Neuchâtel, 2024)
Although laughter is generally associated with humor and was long thought to be uniquely human, growing evidence highlights its existence in other species like primates or rats. Research on nonhuman primates’ laughter emphasizes its emotionality and context-specificity as it mostly occurs during play or when tickled, whereas human voluntary laughter presents such functional flexibility that no classification system seems to exhaust its meaning. Although laughter is identified as a tool to coordinate joint actions by easing transitions between topics and by managing social relationships in humans, these patterns have not yet been investigated in other primates. Focusing on dyadic social play in two species of great apes, bonobos (Pan paniscus) and chimpanzees (Pan troglodytes), we explore the interaction of coordination (transition between moments of an interaction) and social relationships (rank differences and social bond strength) in predicting laughter presence (1/0) and type (contact/non-contact). We show not only that laughter is used to reengage play in apes, but also that non-contact laughter seems to be a specialized coordination tool used to intentionally reengage play-activity in apes, almost absent at other moments of the interaction, be it during the Main Body or at other transition points. Rank differences and social bond strength did not however appear significant predictors neither of laughter presence nor of type. Although the same patterns were observed between species and although laughter quantity was not directly assessed, bonobos showed a higher propensity to laugh during the Main Body of the interaction and when reengaging play than chimpanzees.
Keywords: laughter; bonobo; chimpanzee; social play; joint-action; rank differences; social bond strength; shared intentionality; coordination